Status and seasonal occurrence of birds in Dhaka University campus (Dhaka University Journal of Biological Sciences, 2016)
A study was conducted on the status and seasonal occurrence of the birds in Dhaka University campus, from July, 2013 to February, 2014. During the study period, 54 species of birds belonging to 10 orders, 27 families and 47 genera were recorded. Of the recorded species of birds, 10 (19%) species were found as migrants and 44 (81%) as residents. Out of total species, 14 (26%) were identified as very common, 7 (13%) common, 10 (19%) uncommon, and 23 (43%) as rare. Of the resident species, 14 (25%) were very common residents, 26 (48%) common residents, 3 (6%) uncommon residents, 1 (2%) was rare resident and of the migrants, 7 (13%) were common winter visitors and 3 (6%) were found as uncommon winter visitors. From the study site, 28 (52%) species of passerine birds were observed and remaining 26 (48%) were non-passerines. The highest number of birds was recorded in dry period/winter season (November - February) and the lowest in wet period/monsoon (July - October).Dhaka Univ. J. Biol. Sci. 25(1): 27-37, 2016